Analisis Struktur Kinerja dan Kluster Industri Unggul - Mahindah Mahindah; Farur Rossi; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the performance structure and identify superior industrial clusters in Indonesia. Using secondary data from various sources, this research adopts a quantitative and qualitative approach to evaluate industrial performance based on key economic indicators such as production growth, productivity and contribution to GDP. Cluster analysis techniques are used to group industries that show superior performance. The analysis results show that several industrial clusters, such as high-tech manufacturing and financial services, perform much better than other sectors. These findings provide important insights for policy makers and industry players in formulating more effective and sustainable economic development strategies.